Economics and Law - Abdulkhasan A. M., Shpak A. S., Mashkin A. L., Gogolina E. S., Glagoleva S. V., Miasoedov C. A., Stenkina E. N., Stenkina E. N., Sakharova L. A., Sakharova L. A., Borovkova V. A., Borovkova V. A., Matasova I. I. (Economics and Law, 2020)
the relevance of this study is associated with the improvement of the organization of deposit operations and deposit policy on the example of a bank, today great attention is paid to such aspects in financial activities, in modern realities banks are developing intensively and can provide consumers with a fairly large list of services provided throughout the country
Keywords: финансовый рынок; финансы; financial system; ценные бумаги; система финансов; экономические явления; финансовая среда; financial market; finance; economic phenomena; securities; financial environment; депозитные операции; банковский вклад; депозиты в национальной экономике; deposit operations; bank deposit; deposits in the national economy